Preoperative computed tomography scanning for abdominal neuroblastomas is superior to magnetic resonance imaging for safe surgical planning. Issue 11 (8th August 2019) - Burnand, Katherine; Barone, Giuseppe; McHugh, Kieran; Cross, Kate
Abstract: Background: Cross‐sectional imaging is required to assess disease prior to surgery for neuroblastoma (NBL), and both magnetic resonance imaging (MRI) and computed tomography (CT) scan are considered acceptable. We had concerns that MRI was underestimating disease extent, so from early 2016 we have systematically used MRI and CT before all abdominal NBL resections. The aim of this retrospective study was to establish which imaging modality is more accurate in determining disease extent, particularly after chemotherapy. Methods: Abdominal MRI and CT scans for all children with abdominal NBL referred for surgery from January 2016 to February 2018 were retrospectively reviewed to evaluate the extent of disease and the presence of imaging‐defined risk factors (IDRFs). Results: Thirty‐one patients were eligible for consideration of surgery post disease reassessment with MRI/MIBG. Twenty‐four of 31 children were included. CT was performed a median of 15 (range, 1–47) days after MRI. MRI underestimated IDRFs compared with CT in 13 of 24 patients (54%). Seventeen of 24 patients underwent surgery, and operative findings had 100% correlation with CT imaging. Notably, there were fundamental changes in management post CT in 6 of 24 patients (25%). CT did not underestimate disease compared with MRI in any patient. Conclusion: MRI underestimated the extent of the disease in half of our patients considered for NBL resection. This may be due in part to tumor fibrosis, calcification, and chemotherapy. Preoperative CT scan is the best imaging modality to identify all IDRFs after chemotherapy to ensure safe surgery.